Intervención de enfermería y su influencia en la prevención de tuberculosis en los pacientes que acuden al Centro de Salud Enrique Ponce Luque. Noviembre 2023- abril 2024. - Dávila Lombeida, Andrés Joel (2024)
The interventions carried out by nurses who care for patients with tuberculosis include the task of encouraging them to properly follow the recommended medication plan in order to ensure successful treatment and stop the spread of the disease. In addition, they are dedicated to teaching them about the necessary control measures and offering them emotional support to help them deal with possible psychosocial implications. Aim: Determine nursing interventions and their influence on the prevention of tuberculosis in older adult patients who attend the Enrique Ponce Luque Health Center in the period November 2023-March 2024. Methodology: The project methodology is an experimental study, field, descriptive, transversal and with a qualitative-quantitative approach with a sample of 66 older adult patients treated at the Enrique Ponce Luque Health Center. Results: The result was that the presence of comorbid diseases, low weight, the consumption of harmful substances and a family history of tuberculosis were the main risk factors found; In addition, nursing interventions must be intensified to prevent the disease, as well as improve adherence to treatment if the disease is already established.